Logistics: Analysis of Procurement, Distribution, Warehousing, and Transportation (Mini Review) - Shaqina Nuruly (PT FORMOSA CENDEKIA GLOBAL, 2023)
This scientific article directly with the review literature will describe and prove the results article so that it gets answers with the perspective of researchers and is corroborated from scientific articles from existing literature. The research method in this scientific article uses qualitative by searching for review literature derived from scientific articles in international reputable journals. The findings of scientific articles in literature are made a set with elaboration and this scientific article provides a treasure and additional material for other researchers to use and as a reference. Recommendation to further research that variables other than the findings or used in this research or scientific article can be jointly used in future research, with objects, research methods or produce a new model